Mutation-guided chemotherapy-free strategy in first-line immunotherapy for low PD-L1-expressing non-squamous NSCLC - Hui Li; Liang Zhang; Yu Xu; Jingjing Liu; Guoqiang Wang; Ying Cheng; Shangli Cai; Xinyue Wang; Peng Cui; Shaowei Lan (Journal for ImmunoTherapy of Cancer)
Background The necessity of platinum-doublet chemotherapy in first-line immunotherapy for non-squamous non-small cell lung cancer (nsqNSCLC) with programmed death-ligand 1 (PD-L1) expression on less than 50% of tumor cells remains poorly investigated. Biomarkers predicting this necessity can guide chemotherapy-free treatment to minimize unnecessary toxicity.Methods Treated with immune checkpoint inhibitor monotherapy (ICI-mono), chemotherapy, or combination (ICI-chemo), 790 low PD-L1-expressing nsqNSCLCs (in-house: n=83; public: n=707) were analyzed for development and validation of the interaction score for additional chemotherapy (ISAC). Transcriptomic (public, n=11) and multiplex immunofluorescence data (in-house, n=100) were analyzed to evaluate the immune microenvironment.Results ICI-chemo, compared with ICI-mono, tended to prolong progression-free survival (PFS; HR=0.72, p=0.004) and overall survival (OS; HR=0.77, p=0.071) as first-line therapy in low PD-L1-expressing nsqNSCLCs. The added value of chemotherapy was observed in the ISAC-low subgroup (PFS: HR=0.48, p<0.001; OS: HR=0.53, p=0.001) rather than the ISAC-high subgroup (PFS: HR=1.08, p=0.65; OS: HR=1.14, p=0.56). This predictive utility was independent of tumor mutational burden and PD-L1 expression, indicated by subgroup and multivariable analyses. A high ISAC was associated with adaptive immune resistance reflected by more proinflammatory (eg, CD8+ T cells and M1 macrophages) rather than anti-inflammatory tumor-infiltrating immune cells (eg, M2 macrophages) and high expression of immune checkpoints except for PD-L1 (eg, programmed cell death protein-1).Conclusion A high ISAC was identified as a significant predictor for virtually no added value of platinum-doublet chemotherapy for first-line ICI treatment in low PD-L1-expressing nsqNSCLC. Our findings may help refine personalized therapeutic strategies for nsqNSCLC, thereby improving efficacy and reducing undue toxicity.